The Impact of Individual Expertise and Public Information on Group Decision-Making - Strunz, Ulrich G. (FOM-Edition Research, 2021)
In this open-access-book the author concludes that expertise could be the key factor for global and interconnected problems. Experimental results have shown that expertise was a stronger predictor than public information regarding change in behavior and strategy adaption. Identifying non-routine problem-solving experts by efficient online assessments could lead to less volatile system performance, from which all decision-makers could potentially profit. About the author: Dr. Ulrich G. Strunz is author of books about personal growth and cognitive automatisms. Since 2020 he is CEO of his family business Strunz GmbH and finished his PhD in the field of behavioral economics in the same year. He lectures "Decision-Oriented Management" at FOM Hochschule Munich. .